The effects of maternal body mass index and plurality on maternal and umbilical cord serum magnesium levels in preterm birth at less than 32 weeks of gestation - Yun Sun Choi; Ji Young Hong; Jee Youn Hong; Yoo-Min Kim; Ji-Hee Sung; Suk-Joo Choi; Soo-young Oh; Cheong-Rae Roh; Hye Seon Kim; Se In Sung; So Yoon Ahn; Yun Sil Chang (Korean Society of Obstetrics and Gynecology, 2021)
Objective To evaluate the effects of maternal body mass index (BMI) and plurality on maternal and umbilical cord serum magnesium levels after antenatal magnesium sulfate treatment. Methods This was a retrospective cohort analysis of 135 women treated with antenatal magnesium sulfate at less than 32 weeks of gestation between January 2012 and June 2018. Subjects were stratified into groups according to maternal BMI (group I [18.5-22.9 kg/m2], group II [23.0-24.9 kg/m2], and group III [≥25.0 kg/m2]) and plurality (singleton and twin). Univariable and multivariable analyses were performed to compare the umbilical cord serum magnesium levels between the groups. Results Maternal serum magnesium levels were not significantly different between the maternal BMI groups and singleton and twin pregnancies. Umbilical cord serum magnesium levels were significantly different among the maternal BMI groups (3.3±1.2 mg/dL in group I, 3.3±1.2 mg/dL in group II, and 4.0±1.4 mg/dL in group III, P=0.003). The trend of increase in magnesium levels was statistically significant (P=0.001, Jonckheere-Terpstra test). Umbilical cord serum magnesium levels were not significantly different according to plurality. However, in the multivariable analysis, maternal BMI and plurality were not significantly associated with umbilical cord serum magnesium levels after adjusting for indication and total dose of magnesium sulfate treatment, gestational age at delivery, mode of delivery, neonatal sex, and birth weight. Conclusion Maternal BMI and plurality were not significantly associated with maternal or umbilical cord serum magnesium levels after exposure to antenatal magnesium sulfate treatment.